2021
DOI: 10.5852/ejt.2021.775.1555
|View full text |Cite
|
Sign up to set email alerts
|

On the origin and diversification of the stygobiotic freshwater snail genus Hauffenia (Caenogastropoda: Hydrobiidae) with special focus on the northern species and the description of two new species

Abstract: During systematic surveys of groundwater snails in Slovakia, Hungary and Bosnia and Hercegovina two new species of the genus Hauffenia, H. lozekiana sp. nov. from a single locality in Slovakia, and H. steffeki sp. nov. with a small range in Bosnia and Hercegovina were discovered and are here described based on shell morphology, anatomy and DNA sequence data (COI, 16S rRNA, ITS2). The discovery of H. steffeki sp. nov. extends the range of the genus considerably towards the south. Hauffenia lozekiana sp. nov. ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 768 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…There are subterranean habitats that make migration between caves and springs possible -those are interstitial habitats, unconsolidated sediments bordering and underlying streams and rivers. They are neither rare nor discontinuous (Culver & Sket, 2000;Lamoreaux, 2004;Culver, 2012;Rysiewska et al, 2017;Haase et al, 2021). Falniowski et al (2021a) reported high levels of gene flow, resulting in more than 200 km wide range of one haplotype of the truncatelloid Montenegrospeum bogici (Pešić et Glöer, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are subterranean habitats that make migration between caves and springs possible -those are interstitial habitats, unconsolidated sediments bordering and underlying streams and rivers. They are neither rare nor discontinuous (Culver & Sket, 2000;Lamoreaux, 2004;Culver, 2012;Rysiewska et al, 2017;Haase et al, 2021). Falniowski et al (2021a) reported high levels of gene flow, resulting in more than 200 km wide range of one haplotype of the truncatelloid Montenegrospeum bogici (Pešić et Glöer, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in Montenegrospeum bogici (Pešić et Glöer, 2012) inhabiting caves and interstitial waters in the Western Balkans, and sporadically flooded out in springs, a wide geographic range coupled with high levels of gene flow between local populations was found (Falniowski et al, 2021a). Haase et al (2021) suggest possible dispersal and radiation along the alluvial gravel interstitial, as well as the phreatic rhizosphere (i.e., roots of macrophytes, either aquatic or hygrophilous plants) for Hauffenia Pollonera, 1898, a stygobiont snail inhabiting only interstitial waters, not caves in Slovakia. Although stygobites (e.g., Montenegrospeum mentioned above) tend to have wider geographic ranges than subterranean terrestrial troglobites (Lamoreaux, 2004).…”
Section: Introductionmentioning
confidence: 95%
“…The central Western Carpathians formed an island in the Paratethys during the Burdigalian and Langhian stages of the Miocene, which ranged from 20.4 to 13.6 Mya (Kováč et al, 2017). This longterm isolation undoubtedly led to the independent evolution of the local biota after previous colonization of the territory by lineages from southern European orogenic units (e.g., Kováč, et al 2014;Haase et al, 2021). The onset of cooling of the contemporary global climate, known as the Middle Miocene Climatic Transition-MMCT (Methner et al, 2020), could promote the colonization of deep subterranean spaces by edaphic invertebrates.…”
Section: Divergence Time Of the Subterranean Pseudosinella Lineagesmentioning
confidence: 99%
“…The central Western Carpathians formed an island in the Paratethys during the Burdigalian and Langhian stages of the Miocene, which ranged from 20.4 to 13.6 Mya (Kováč et al, 2017). This longterm isolation undoubtedly led to the independent evolution of the local biota after previous colonization of the territory by lineages from southern European orogenic units (e.g., Kováč, et al 2014;Haase et al, 2021). The onset of cooling of the contemporary global climate, known as the Middle Miocene Climatic Transition-MMCT (Methner et al, 2020), could promote the colonization of deep subterranean spaces by edaphic invertebrates.…”
Section: Divergence Time Of the Subterranean Pseudosinella Lineagesmentioning
confidence: 99%